Endotracheal Use of Perfluorane in Patients with Acute Respiratory Distress Syndrome Under Artificial Ventilation - V. V. Moroz; D. A. Ostapchenko; A. V. Vlasenko; P. Yu. Osipov; L. V. Gerasimov (Общая реаниматология)
The paper presents the results of a comparative study of different routes of intrapulmonary administration of perfluorane under artificial ventilation in patients with acute respiratory distress syndrome of various genesis. It shows the advantages and disadvantages of these routes, their impact on gas exchange, pulmonary biomechanical properties, cardiac hemodynamics, the transport and uptake of oxygen, the duration of respiratory support, and the length of stay in an intensive care unit.